Acute perforation in a gastrojejunocolic fistula after a laparascopic Roux-en-Y gastric bypass: case report - Jos Velleman; Benoit Masereel; Paul Geyskens (Surgical Case Reports, 2023)
Abstract Background Gastrojejunocolic fistulas are a rare type of fistulas after a laparascopic Roux-en-Y gastric bypass (LRYGB). They are known as a chronic complication. This case report is the first to describe an acute perforation in a gastrojejunocolic fistula after LRYGB. Case presentation A 61-year-old woman with a history of a laparascopic gastric bypass was diagnosed with an acute perforation in a gastrojejunocolic fistula. A laparascopic repair was performed by closing the defect in the gastrojejunal anastomosis as well as the defect in the transverse colon. However, 6 weeks later, a dehiscence of the gastrojejunal anastomosis occured. This was reconstructed by an open revision of the gastric pouch and gastrojejunal anastomosis. Long-term follow up showed no recurrence. Conclusions Combining the findings of our case with other literature, a laparoscopic repair with wide resection of the fistula, a revision of the gastric pouch and gastrojejunal anastomosis as well as closing the defect in the colon seems to be the best approach in case of an acute perforation in a gastrojejunocolic fistula after LRYGB.